Study on ultraviolet radiation effects on bonding interactions between lubricants and diamond-like carbon overcoat - Shi, Gladys Yuhui. (2009)
Pushing recording density towards even more data storage per unit area and beyond requires reducing flying height to 2.5nm-3nm or below. This raises tribology issues regarding the head disk interface (HDI) and prompts for urgent solutions.